2016
DOI: 10.1042/bj20151150
|View full text |Cite
|
Sign up to set email alerts
|

Role of Munc13-4 as a Ca2+-dependent tether during platelet secretion

Abstract: The Munc13 family of exocytosis regulators has multiple Ca2+-binding, C2 domains. Here, we probed the mechanism by which Munc13-4 regulates in vitro membrane fusion and platelet exocytosis. We show that Munc13-4 enhances in vitro SNARE-dependent, proteoliposome fusion in a Ca2+- and phosphatidylserine (PS)-dependent manner that was independent of SNARE concentrations. Munc13-4-SNARE interactions, under the conditions used, were minimal in the absence or presence of Ca2+. However, Munc13-4 was able to bind and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…However, it has recently been demonstrated that (1) NK cell cytotoxicity has a distinct immunoregulatory role in HLH disease, 19 and (2) Munc13-4 has a critical function in platelets and neutrophils. [20][21][22][23] By using an LV coding for a Munc13-4/GFP fusion protein, our present study demonstrated that gene transfer into murine HSCs resulted in transgene expression in all the hematopoietic lineages, including NK and myeloid cells. Thus, HSC gene correction (providing multilineage Munc13-4 expression) might be a valuable treatment option for FHL3 in patients.…”
Section: Discussionmentioning
confidence: 92%
“…However, it has recently been demonstrated that (1) NK cell cytotoxicity has a distinct immunoregulatory role in HLH disease, 19 and (2) Munc13-4 has a critical function in platelets and neutrophils. [20][21][22][23] By using an LV coding for a Munc13-4/GFP fusion protein, our present study demonstrated that gene transfer into murine HSCs resulted in transgene expression in all the hematopoietic lineages, including NK and myeloid cells. Thus, HSC gene correction (providing multilineage Munc13-4 expression) might be a valuable treatment option for FHL3 in patients.…”
Section: Discussionmentioning
confidence: 92%
“…While it is difficult to distinguish between these possibilities, three lines of argument support a loss of tethering interpretation. Firstly, the shape of the MSD curve in the scinderin knockdown cells has a relatively constant slope, indicative of unconstrained motion, similar to that seen in Munc13-4 knockout platelets (Chicka et al, 2016), although this could also reflect a confounding combination of active transport (positive change in slope) and caging (asymptotic slope). Secondly, in these experiments scinderin knockdown and actin depolymerization have similar effects on vesicle mobility, which is consistent with a comparable mechanism of action, specifically a reduction in actin dependent vesicle tethering.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we examined secretory vesicle motion in platelets (Chicka et al, 2016), and we used the same approach to quantify the mobility of secretory vesicles in PC12 cells. Through tracking the visual center of mass of the vesicles over time, we can build up a description of the vesicles displacement over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It is thought to work with the small GTPase, Rab27, to bring granule and plasma membranes together and thus promote Soluble NSF-Attachment Protein Receptor (SNARE) protein-mediated membrane fusion. 16 Does this mean SNAREs are not involved in PDI exteriorization? Perhaps, but there are a number of SNAREs present in platelets, not all of which may require Munc13-4 for function.…”
mentioning
confidence: 99%